Enhance heat transfer in the channel with V-shaped wavy lower plate using liquid nanofluids. (March 2015) - Abed, Azher M.; Sopian, K.; Mohammed, H.A.; Alghoul, M.A.; Ruslan, Mohd Hafidz; Mat, Sohif; Najah Al-Shamani, Ali
Abstract: The heat transfer and flow characteristics in corrugated with V-shape lower plate using nanofluids are numerically studied. The computations are performed on uniform heat flux over a range of Reynolds number (Re) 8000–20, 000. The governing equations are numerically solved in the domain by a finite volume method (FVM) using the k – ε standard turbulent model. Studies are carried out for different types of nanoparticles Al2 O3, CuO, SiO2 and ZnO with different volume fractions in the range of 0–4%. Three different types of base fluid (water, glycerin, ethylene glycol) are also examined. Results indicated that the average Nusselt number for nanofluids is greater than that of the base liquid. The SiO2 nanofluid yields the best heat transfer enhancement among all other type of nanofluids. Heat transfer enhancement increase with increases the volumetric concentration, but it is accompanied by increasing pressure drop values. Moreover, the average Nusselt number increases with an increase in Reynolds number and volume concentration. The SiO2 –glycerin nanofluid has the highest Nusselt number compared with other base fluids. The present study shows that these V-shaped wavy channels have advantages by using nanofluids and thus serve as promising candidates for incorporation into efficient heat transfer devices.